Analisis Pengaruh Shopping Lifestyle dan Fashion Involvement Terhadap Impulse Buying Behavior - Melkyory Andronicus; Lyza Tahura Chairunnisa; indah rizky aryanti (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
The research was done at Zara and H&M customers in the famous shopping mall in Medan. The purpose of this research was to know the influence given by Shopping Life Style and Fashion involvement on Impulse Buying Behavior in consumer buying activity. The type of research used was associated with the study population which was consumers who visited Sun Plaza Medan with an estimated 950 people per day except for Saturday and Sunday. The sampling was a random sample with the Slovin formula so the number of samples was 91 respondents. Sources of research data that was primary data with data collection technique that was survey and observation. Data analysis techniques used multiple linear regression, classical assumption test, and hypothesis test. Based on the results of the research conducted, it could be submitted that partially and simultaneously Shopping lifestyle and Fashion involvement significantly influenced impulsing buying behavior study at ZARA and H & M consumers in Sun Plaza Medan. Shopping lifestyle and Fashion involvement have a very strong relationship with impulsing buying behavior. Impulsing buying behavior could be explained by Shopping lifestyle and Fashion involvement equal to 80,6% and the other equal to 19,4% could be explained by another variable which not examined.